2008
DOI: 10.1007/978-3-540-70587-1_1
|View full text |Cite
|
Sign up to set email alerts
|

A Role-Based Infrastructure for the Management of Dynamic Communities

Abstract: Abstract. This paper defines an operational framework for specifying and establishing secure collaborations between autonomous entities that need to interact and depend on each other in order to accomplish their goals, in the context of mobile ad-hoc networks. We call such collaborations mission-oriented dynamic communities. We propose an abstract model for policy-based collaboration that relies on a set of task-oriented roles. Nodes are discovered dynamically and assigned to one or more roles, and then enforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In contrast, a fresh JamVM and rmiregistry setup use about 3,200 KB and 5,900 KB respectively, whereas a JamVM running an empty Ponder2 instance and rmiregistry use about 8,200 KB and 5,900 KB respectively. The small memory footprint needed for the policy management infrastructure highlights that other devices with a similar configuration and capacity could also be used [22]. …”
Section: A Scalability Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a fresh JamVM and rmiregistry setup use about 3,200 KB and 5,900 KB respectively, whereas a JamVM running an empty Ponder2 instance and rmiregistry use about 8,200 KB and 5,900 KB respectively. The small memory footprint needed for the policy management infrastructure highlights that other devices with a similar configuration and capacity could also be used [22]. …”
Section: A Scalability Concernsmentioning
confidence: 99%
“…The Gumstix has an Intel XScale PXA255 400 MHz processor with 16 MB flash memory and 64 MB SDRAM, running Linux, Wi-Fi enabled, and executing the lightweight JamVM 4 . It has been shown in [22] that the size of the bytecodes required for running Ponder2 and necessary libraries is only 710 KB. In terms of memory usage, it was observed that a Gumstix storing in memory a specification containing about 25 policies required 15 MB for the Ponder2 process and 9,224 KB for the rmiregistry process.…”
Section: A Scalability Concernsmentioning
confidence: 99%
“…Note that some bindings may be event triggered. When a pattern is instantiated, actual SMCs may be passed as parameters, or alternatively an assignment policy [4] may specify under which conditions a subsequently discovered SMC should be assigned to the respective role. A pattern is typically instantiated at a SMC, which will be responsible for enforcing the architectural styles defined in the pattern.…”
Section: A Patterns Of Interactionmentioning
confidence: 99%
“…We focus on interactions for the design of a health monitoring application in the medical domain. However, the same principles have also been applied in a related project to the management of ad-hoc communities of unmanned autonomous vehicles (UAVs) for surveillance missions in hostile environments [4].…”
Section: Introductionmentioning
confidence: 99%
“…We base our work on existing research in the field of Multi-Agents Systems [7] and the Web of Things [3,1], which form both an inspiration and an underlying layer for the present work.…”
Section: Introductionmentioning
confidence: 99%